Investigating the Efficacy of Multimodal Interactive learning Materials in Enhancing Speaking Proficiency of English Foreign Language Learners at MA Al Jariyah NWDI San Baro - Budiman Budiman; M. Adib Nazri; Siti Maysuroh; Laila Wati (Journal on Education, 2024)
This study investigates the efficacy of using multimodal interactive learning materials in enhancing the speaking proficiency of English foreign language learners at MA Al-Jariyah NWDI San Baro. The study was conducted through a case study approach. The participant was grade 11 that consist of 15 students (5 males and 10 females) and selected using purposive sampling. This study used non-test instruments: close-ended questionnaire, document, and structured interview. Data collection for this research involved interviews, questionnaires, journal articles, and recording. The data analysis procedure of this study followed Miles and Hubermen in 1984 which covered from data reduction, data interpretation, and drawing a conclusion. The English foreign language learners in Indonesia face some obstacles in learning English such as motivation, anxiety, grammar difficulties, limited practice opportunities, lack of confidence, and embarrassment due to mistake. The results of this study show that multimodal interactive learning materials are effective in enhancing speaking proficiency among English foreign language learners. The conclusion of this study is that multimodal interactive learning materials can help English foreign language learners improve their speaking skills in a more dynamic and interactive manner.